Cowden Syndrome with a Novel Germline PTEN Mutation and an Unusual Clinical Course - Seol, Jung Eun (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2015)
Here, we report a case of Cowden syndrome with an unusual clinical course of late-onset oral papillomatosis and a novel germline PTEN mutation. Cowden syndrome is the most common phosphatase and tensin homolog hamartomatous tumor syndrome. It is characterized by multiple hamartomas in the gastrointestinal tract and mucocutaneous lesions such as trichilemmomas, oral papillomatosis, facial papules, and acral keratoses. Patients with Cowden syndrome have a higher risk of malignancies, especially breast, colon, and thyroid cancers. A 53-year-old female presented with cobblestone-like papillomatous papules on the lower gums that developed 1 year earlier. She had no other mucocutaneous lesions besides oral papillomatosis. Gastrointestinal endoscopy and colonoscopy revealed multiple hamartomas in the stomach and colon. The patient had a history of breast cancer and multinodular goiter diagnosed 4 and 5 years ago, respectively. She was diagnosed with Cowden syndrome and a novel PTEN mutation was confirmed by direct sequencing.